Is exposure to hydrocarbons associated with chronic kidney disease in young Nigerians? A case–control study - Okoye, Ogochukwu Chinedum; Awunor, Nyemike (Frontiers in Nephrology, 2022)
Introduction Although environmental exposure to hydrocarbons have been linked to non-communicable diseases, its association with chronic kidney disease (CKD) is still an emerging area. Epidemiological studies associating CKD with prolonged exposure to hydrocarbons have mostly focused on occupational exposure with fewer on exposure from residing in contaminated areas. The aim of this study was to determine any association between long term exposure to hydrocarbons and the risk for CKD by comparing the residence and occupational history of young CKD patients with non-CKD controls. Materials and Methods A case-control study of 74 cases and 74 age and sex-matched non-CKD controls. Cases were young (18-44years) patients diagnosed with suspected chronic glomerulonephritis recruited from the outpatient clinics and medical wards. Patients with CKD from traditional causes were excluded. Data were collected using a pre-tested researcher-structured questionnaire adapted from WHO STEPS. To assess exposure, a detailed work history and all residential addresses where the patients have spent one year and above were recorded. ‘Exposed’ was regarded as long-term (at least one year) residence in a known oil polluted area; jobs involving crude oil exploration, processing, transportation, sales, and clean-up of crude oil hazards. Absence of a history of chronic exposure or any form of exposure were regarded as ‘less exposed’. Results: Fifty-two (70.3%) cases were categorised as exposed compared to twenty-one (28.4%) of controls (p<0.001). Thirty-four (45.9%) cases were born near petrochemical industries compared to 11 (14.9%) controls (p=<0.001); thirty-four (45.9%) cases were residing near petrochemical industries compared to eight (10.9%) controls (p=<0.001). When asked ‘do you think you have been significantly exposed to crude oil?’, fifteen (20.3%) cases answered yes compared to only two (2.7%) among controls (p=<0.001). Conclusion: Our findings suggest an association between exposure to petrochemicals and CKD in young Nigerians diagnosed with suspected CGN. Exposure is significantly associated with a higher mean age, waist circumference and blood sugar; however other traditional risk factors of CKD were not considerably more prevalent in this unique patient population. These findings should prompt more emphasis on occupational history, residential history and other relevant environmental exposures in the assessment of patients at risk for CKD